Effects of biofilm and gastropod grazing on barnacle cyprid settlement in a mangrove rehabilitation site, Sg. Besar, Selangor, Malaysia / Wong Jin Yung - Wong, Jin Yung (2014)
Biofouling by barnacles is a problem commonly encountered in mangrove replanting projects. This study examined the effect of biofilm and snail grazing on settlement of cyprids and proposed solution to control biofouling. An effective identification tool for barnacle cyprids was first built to facilitate the study as the barnacle cyprids are very difficult to identify. Several species of wild-caught barnacle cyprids from Matang Mangrove Forest Reserve waters were studied. The cyprids were identified through DNA barcoding analysis. Their morphological characters, both qualitative and quantitative, were studied and used to develop a morphology-based classification model to facilitate classification on large scale. Compared to using linear measurements only, inclusion of the qualitative carapace sculpturing character greatly improved the classification model. Field experiments were conducted to test the settlement preference of barnacles on substrates without and with biofilms of different ages. Higher number of barnacle settlement was found on substrates with aged biofilms compared to susbtrates without or with young biofilms. Characterization of biofilm successional profiles with respect to their bacterial and microeukaryotic compositions and biofilm structure were also carried out. Significant association was found between the successional changes in microeukaryote composition and the settlement of barnacle, but not with the bacterial composition or biofilm structure. All three successional profiles (bacteria, microeukaryotes, biofilm structure) were quantitatively shown to be concordant, indicating likely interactions among them and warrant future studies. Naturally-grown mangrove trees were observed to be less prone to biofouling than artificial substrate and re-planted mangroves. Abundant snail grazers were observed in the natural mangroves and exclusion experiments were conducted. Results showed that exclusion of grazers led to settlement of large number of barnacles and higher growth of microbial biofilms, suggesting grazing pressure, not anti-fouling activity from the trees, as the underlying factor regulating barnacle abundance on natural mangrove trees. Study on the snail behaviour was carried out to understand why grazing pressure on barnacles was not established in the re-planted mangrove plants. While strong collective movements and grazing activity of snails in tandem with the tidal cycle (to avoid submersion) were observed in natural mangrove trees, it may be difficult for such behaviors to form on replanted mangrove seedlings.